Advances in Mechanical Engineering Selected Contributions from the Conference (3z(BModern Engineering: Science and Education(3y(B, Saint Petersburg, Russia, June 2021 /s - Evgrafov, Alexander N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book draws together the most interesting recent results to emerge in mechanical engineering in Russia, providing a fascinating overview of the state of the art in the field in that country which will be of interest to a wide readership. A broad range of topics and issues in modern engineering is discussed, including dynamics of machines, materials engineering, structural strength and tribological behavior, transport technologies, machinery quality and innovations. The book comprises selected papers presented at the 10th conference "Modern Engineering: Science and Education", held at the Saint Petersburg State Polytechnic University in June 2021 with the support of the Russian Engineering Union. The authors are experts in various fields of engineering, and all of the papers have been carefully reviewed. The book will be of interest to mechanical engineers, lecturers in engineering disciplines and engineering graduates.
Blended Learning of Higher Mathematics in the Century of the Digitalization of Education -- Influence of the Control Object Mass on the Stability Region -- A Method for Increasing the Speed Discreteness in test Centrifuges Based on Sew-Eurodrive -- Internal Vibration Active of Machines with Elastic Transmission Mechanism.
Keywords: Machinery; Industrial engineering; Production engineering; Building materials; Machinery and Machine Elements; Industrial and Production Engineering; Structural Materials; Mechanical engineering -- Congresses; Mechanics, Applied -- Congresses